Alterations within the Osteo-Hematopoietic Niche in MDS and their Therapeutic Implications - Mies, Anna; Bulycheva, Ekaterina; Mandac Rogulj, Inga; C. Hofbauer, Lorenz; Platzbecker, Uwe- (Current Pharmaceutical Design, 2016)
Hematopoietic and mesenchymal stem and progenitor cells are organized in the osteo-hematopoietic niche, a complex microenvironment ensuring self-renewal and differentiation. Perturbations of the niche architecture, the mutual cellular interactions and signaling pathways disrupt tissue homeostasis resulting in cytopenia and malignant diseases such as myelodysplastic syndromes (MDS), supporting the concept of niche-induced oncogenesis. Analyzing the available treatment options for patients harboring MDS, it becomes evident that many of them specifically modify components of the stem cell niche. Hereby especially compounds inhibiting the TGF-β superfamily seem to represent a promising novel approach for patients with anemia as a result of ineffective erythropoiesis. Moreover, apart from affecting tumorigenesis, these drugs appear to influence bone structure and function as well as hematopoiesis in elderly MDS patients with a disturbed microarchitecture of the bone marrow. In the present review we will dissect the contribution of components of the stem cell niche for the pathogenesis of MDS and discuss current therapeutic strategies targeting components of the niche, focusing on the modulation of TGF-β signaling.
Keywords: signaling